Factors Shaping the Cognitive Dissonance of Online Consumers (Study of Fashion Products on Shopee in Indonesia) - Edy, Irwan Christanto (Formosa Journal of Science and Technology, 2025)
The study aims to determine the influence of websites on emotion-mediated and cognitive dissonance and moderated lifestyle and gender. The research uses a quantitative approach. The novelty of research is cognitive dissonant behavior by examining its constituent factors. Respondents include the millennial generation who buy fashion products on Shopee. Purposive sampling method. The data collection technique uses a closed questionnaire. The data is statistically analyzed with SEMPLS. The findings of the analysis showed that cognitive dissonance was positively and significantly influenced by lifestyle. The implication of this research is that in online business, every marketer, especially fashion products, must understand the characteristics of the lifestyle that develops in society. Lifestyle is a very strong shaping factor in cognitive dissonance purchasing decisions.